2016
DOI: 10.1111/ijcp.12878
|View full text |Cite
|
Sign up to set email alerts
|

Process quality indicators for chronic kidney disease risk management: a systematic literature review

Abstract: Based on this review, sufficiently validated QIs can be selected for measuring the quality of CKD care. This review provides insight in QIs that need further validation, and in areas of care where QIs are still lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
3
0
2
Order By: Relevance
“…10 For this reason, this clinical support tool has been used as a reference by several authors, in order to guide, standardize and optimize the conduct of these professionals. 18,19,20,21,22 Due to the fact that there is no instrument available in Brazil to guide the evaluation of pharmacotherapy, specifically in the population of patients with CKD, our group performed the translation and cross-cultural adaptation of PAIR at an initial phase (Chart 1). 23 The present study aimed to validate the PAIR, assessing its reliability, validity and responsiveness, as well as the prevalence of DRP in a sample of patients with CKD undergoing conservative treatment at a local nephrology outpatient service.…”
Section: Abstract Introductionmentioning
confidence: 99%
“…10 For this reason, this clinical support tool has been used as a reference by several authors, in order to guide, standardize and optimize the conduct of these professionals. 18,19,20,21,22 Due to the fact that there is no instrument available in Brazil to guide the evaluation of pharmacotherapy, specifically in the population of patients with CKD, our group performed the translation and cross-cultural adaptation of PAIR at an initial phase (Chart 1). 23 The present study aimed to validate the PAIR, assessing its reliability, validity and responsiveness, as well as the prevalence of DRP in a sample of patients with CKD undergoing conservative treatment at a local nephrology outpatient service.…”
Section: Abstract Introductionmentioning
confidence: 99%
“…Nutritional guidance was not very prominent among the primary list of recommendations we based our questionnaire on. This can explain why previous work indicated a lack of QIs concerning lifestyle management [32]. Our final list of QIs included 1 indicator concerning lifestyle management.…”
Section: Principal Findingsmentioning
confidence: 95%
“…In the past QIs for evaluating processes and outcomes of CKD care have been developed and although a systematic review identified 273 QIs, few QIs are available that focus on primary care, integrated management between primary and secondary care and EMR extractability to allow automatic audit and feedback [30][31][32][33]. Patients are also rarely involved in the design of the QIs even though a study which investigated the conservative management of kidney failure indicated that there is a discordance between QIs important for patients and for caregivers [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…O PAIR é o primeiro e único instrumento desenvolvido para farmacêuticos e profissionais de saúde que atuam em nefrologia, com foco na segurança da medicação, que permite a identificação e o manejo de PRMs de forma rápida e sistemática 13 . Por essa razão, essa ferramenta de suporte clínico, tem sido utilizada como referência por diversos autores, a fim de orientar, padronizar e otimizar a conduta desses profissionais [14][15][16][17][18] .…”
Section: Introductionunclassified
“…Além disso, a utilização de um registro padronizado pode gerar dados que permitem avaliar comparativamente o impacto da assistência na qualidade e na segurança do uso de medicamentos, assim como incentivar ações de melhorias entre os serviços de nefrologia 14,16 .…”
Section: Introductionunclassified